2011
DOI: 10.1007/s12088-011-0214-2
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Plasmid-Mediated AmpC β-Lactamases Among Escherichia coli and Klebsiella pneumoniae Clinical Isolates in a Tertiary Care Hospital in Bangalore

Abstract: Therapeutic options for infections caused by gram-negative organisms expressing plasmid-mediated AmpC b-lactamases are limited because these organisms are usually resistant to all the b-lactam antibiotics, except for cefepime, cefpirome and the carbapenems. These organisms are a major concern in nosocomial infections and should therefore be monitored in surveillance studies. Hence, this study was aimed out to determine the prevalence of plasmid-mediated AmpC b-lactamases in E. coli and K. pneumoniae from a ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
2
8
0
2
Order By: Relevance
“…32 Most studies showed 100% sensitivity toward imipenem. 33,22,34 Incidences of meropenem resistance higher than that of imipenem among nosocomial pathogens was observed by Gupta et al, 35 The resistance exhibited in our case is due to existence of carbapenemase producing isolates in our setting. This may be because patients in Intensive Care Unit are directly being treated with carbapenems that has led to development of such multidrugresistant isolates in our health-care setting.…”
Section: Resultssupporting
confidence: 49%
“…32 Most studies showed 100% sensitivity toward imipenem. 33,22,34 Incidences of meropenem resistance higher than that of imipenem among nosocomial pathogens was observed by Gupta et al, 35 The resistance exhibited in our case is due to existence of carbapenemase producing isolates in our setting. This may be because patients in Intensive Care Unit are directly being treated with carbapenems that has led to development of such multidrugresistant isolates in our health-care setting.…”
Section: Resultssupporting
confidence: 49%
“…Bir diğer sorun ise, porin kaybı ve/veya yüksek düzeyde kromozomal AmpC üretiminin benzer fenotiplere yol açabilmesidir. Bu birleşik mekanizmalar özellikle E.coli'de görülmektedir 10,11 . pAmpC üreten izolatların belirlenmesinde, genişle-tilmiş spektrumlu sefalosporinler (seftazidim, sefotaksim) ve sefoksitin direncine sahip izolatların seçilmesi önerilen bir yöntemdir 12 .…”
Section: Introductionunclassified
“…In the present study 28.7% of the isolates were found to be plasmid mediated AmpC producer which is higher compared to other studies from India. Study from Chennai during 2005 reveals 20.8% AmpC producers whereas study from Bangalore during 2012 reveals 7.7% as AmpC producers among K pneumonia (Sasirekha et al, 2012). Studies also reveal a relatively higher percentage of these enzymes when compared to earlier report of 2.2% for K pneumoniae isolates in Karnataka (Ratna et al, 2003).…”
Section: Resultsmentioning
confidence: 81%